2012
DOI: 10.1177/147470491201000205
|View full text |Cite
|
Sign up to set email alerts
|

Human Nonindependent Mate Choice: Is Model Female Attractiveness Everything?

Abstract: Abstract:Following two decades of research on non-human animals, there has recently been increased interest in human nonindependent mate choice, namely the ways in which choosing women incorporate information about a man's past or present romantic partners ('model females') into their own assessment of the male. Experimental studies using static facial images have generally found that men receive higher desirability ratings from female raters when presented with attractive (compared to unattractive) model fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…This is argued to be because, while most individuals form partnerships, only individuals of high mate quality are likely to have highly attractive partners: an attractive individual’s mate choices are therefore potentially the best indicator of mate quality (e.g. 11 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is argued to be because, while most individuals form partnerships, only individuals of high mate quality are likely to have highly attractive partners: an attractive individual’s mate choices are therefore potentially the best indicator of mate quality (e.g. 11 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study, like many others in the human 6 , 7 , 13 and animal 30 literature, focuses on the choices of females. The reason for this focus is that previous work suggests that mate-choice copying is more likely to be adaptive for women than for men, because long-term ‘mate value’ is more difficult to assess in men 13 . Any content-specific social learning mechanisms for mate choice should, therefore, be particularly detectable in women.…”
Section: Introductionmentioning
confidence: 99%
“…Our first hypothesis was that we would successfully replicate Hill and Buss (2008)'s Experiment 1 (both the desirability enhancement effect in females and the desirability diminution effect in males). Vakirtzis and Roberts (2012) found evidence that desirability ratings between heterosexual men's and homosexual women's rating of a target woman did not differ, and while differences in sexual orientation exist, a large portion of male and female homosexual preferences tend to line up with their respective same-sex heterosexual counterparts. By extending Hill and Buss to include homosexual participants, we therefore also predicted in our second hypothesis that homosexual males would exhibit desirability diminution effects (similar to heterosexual males) when viewing male targets surrounded by females.…”
Section: Predictionsmentioning
confidence: 95%
“…Mate-copying tendencies can be manifested in various forms of behavior. Research by Vakirtzis and Roberts (2012) used marital status of the male model to evaluate how women rate the attractiveness of the male model and found that married men are more desirable than single men. Other methods used to provide evidence for matecopying tendencies include forming simulated attraction (Dunn & Doria, 2010).…”
Section: Introductionmentioning
confidence: 99%